Vozes femininas : a polifonia arquetípica em Florbela Espanca - Bomfim, Renata Oliveira (2009)
This research proposes some reflections regarding de social voices and perfect models present in the sonnet books Livro de Mágoas (1919), Livro de Sóror Saudade (1921), Charneca em Flor (1930) e Reliquiae (1931), from the Portuguese poetess Florbela Espanca. Therefore we will use as basic theoretical mark, the works of Mikhail Bakthin, specially the concepts of dialogism and polyphony, and of Carl Gustav Jung, the concepts of perfect models and collective unconscious. The poetic of Florbela Espanca is polyphony because it embraces a multiplicity of social voices and its respective speeches, she is also a perfect model, because she reproduces experiences that go beyond the personal ambit, finding resonance in t e collective of different times. Among those perfect models feminine voices expressed into her poetry, we will analyze those of Lilith, Eva and Mary. This representations embrace aspects such as the sensuality, the eroticism, the clerical and virginal aspirations, the pain, the anxiety, the desire and the vanity, themes that reflect certain desires of making dialectics dialog, we have opposites that, in a father based society can t reach the complete expression. The hardship of professional and personal realization of a woman in a traditional society like the one in the first quarter of the 20th century, in that case Florbela, was generated from a anxiety in the poetess that drove her to suicide, fate that we interpreter as modern tragedy , in the raymondian framework. The difficulties found by woman in a patriarchal world, is poetically worked by Florbela that respond with a text marked by the uneasiness, by the search and by wish of finding, in the utopia of Frederic Jameson, a way of expression from the plea of the paradigm that come from duality, demonstrated by the desire of infinity and integration with nature. The literate critic, Maria Lúcia Dal Farra, will be the base fundament in what approaches the life and work of Florbela Espanca, and other authors will help in the construction of this mosaic research that, has as a goal to be interdisciplinary.